Effect of nylon fabric reinforcement on the mechanical performance of adhesive joints made between glass and GFRP. - P. Munaf; F. Marchione; G. Chiappini; M. Marchini (Fracture and Structural Integrity)
The use of reinforcements in adhesive joints makes the stress distribution more uniform, improving their mechanical performance and adhesion. The present paper aims to verify the effectiveness and efficiency of the insertion of nylon 6 fabric in the adhesive layer, to study their applicability and functionality in building components. The increase in stiffness achieved by applying nylon 6 fabric in the adhesive layer between glass and GFRP pultruded profiles and steel laminates applied to GFRP beams is investigated. Three different epoxy adhesives and one epoxy resin are used and compared. Three different types of tests are carried out in order to study the different properties of the reinforcement system: tensile tests on GFRP/GFRP single-lap adhesive joints, with and without nylon fabric reinforcement; tensile tests on double-lap adhesive joints between float glass and pultruded GFRP profiles reinforced with nylon fabric according to four configurations (in the middle plane of the adhesive layer, on the glass surfaces, on the GFRP surfaces, on both GFRP and glass configurations) to verify the influence of its position; three-point bending tests on long GFRP tubular profiles reinforced with steel plates and nylon fabric in different configurations, to study resistance to bending loads. The results from the experimental campaign show the effectiveness of the reinforcement system using nylon fabric 6. In general, both a reduction in ultimate strength and an increase in joint stiffness compared to unreinforced configurations are observed.